Copper electrodeposition on silicon electrodes. (2018) - Lima, F.; Mescheder, U.; Müller, C.; Reinecke, H.
A two-step process is reported for the electrochemical deposition of copper layers on n-type silicon substrates using an acidic copper sulphate solution without addition of additives and no light assistance. Metal layers were generated on electrodes with different crystal orientations. The process consists of a combination of two very common techniques: chronoamperometry and pulse plating. The former technique is applied to obtain an instantaneous nucleation on the working electrode. Therefore, a large amount of metal nuclei is formed on the substrate before the pulse technique starts. The latter is, then, used to grow the particles previously generated and form a homogeneous metal layer with full coverage onto the semiconductor electrodes. The potential magnitudes are carefully chosen in line with energy levels observed at the semiconductor-electrolyte interface and were also calculated in this work.